Assessing multistakeholder processes: Needs and possible responses in three CGIAR Initiatives - Andersson, Krister (CGIAR System Organization, 2023)
Multistakeholder processes (MSPs) are becoming increasingly important in international development research. MSPs are defined as “purposefully organized interactive processes that bring together stakeholders to participate in dialogue, decision-making and/or implementation regarding actions seeking to address a problem they hold in common or to achieve a goal for their common benefit” (Sarmiento Barletti- et al 2020). The main rationale for promoting MSPs within One CGIAR research activities is that well-organized MSPs can help ensure that the research is trusted and used by the intended users of research (Matson et al 2016). It also provides the means for more equitable and democratic decision making to guide the research process, making sure that the defined research priorities reflect questions and topics that the group of stakeholders consider important (Larson et al 2022). Many CGIAR Researchers and their partners now consider MSPs as the most appropriate way of engaging stakeholders in research activities with the goal of generating meaningful, long-lasting impacts. CGIAR Researchers are also learning that to make MSPs work effectively, it is not enough to merely invite people to the table; these processes need to become a space where participants can begin to address questions of power, equity and buy-in (Baker et al 2021). More specifically, previous research has found that MSPs are effective when the organizers of these processes are able to: (a) elevate the voices of marginalized groups; (b) build trust by helping actors understand others’ perspectives and the value of meaningful, equitable collaboration; (c) support conflict resolution and (d) foster social learning through self-assessment and reflection (Brouwer et al 2016). One of the central challenges facing the CGIAR currently is to develop an approach to MSPs that not only embraces these principles, but is also practical, flexible and not too costly.